PENGARUH PEMBELAJARAN DARING TERHADAP MINAT BELAJAR SISWA PADA MASA COVID-19 - Abdulloh, Abdulloh; Dedi, Fransisca S.O. (STKIP PGRI Bandar Lampung, 2021)
During this pandemic, the learning process changed from face-to-face to distance learning (online), including at SMK Negeri 6 Bandar Lampung which implemented distance learning with the guidance of parents from home and teachers from school. This has an impact on students' interest in learning. This research was carried out on how online learning had an effect on student interest in learning at SMK Negeri 6 Bandar Lampung during the Covid-19 period. This research uses qualitative research methods with descriptive data analysis, so that it is easy to understand. Students interact in learning with the school using several applications in the form of a Learning Management System (LMS), a software application for online activities, electronic learning programs (e-learning programs), Google Classrom, zoom, Whatsapp Group, Google Meet, and Quizizz . Respondents taken are students, parents, and teachers. Based on the results of research from 30 students who filled out the form, there were 20 students or 62.5% who felt boredom following online learning and 10 people or 37.5% were still relaxed or did not experience boredom while participating in online learning. It can be concluded that the online learning process is very influential on students' interest in learning.